Valuation : measuring and managing the value of companies - Koller, Tim; Goedhart, Marc H.; Wessels, David (Wiley finance series., 2020)
"Valuation lies at the crossroads of corporate strategy and finance. In today's economy, it has become an essential role -- and one that requires excellence at all points. This guide shows you everything you need to know, and gives you the understanding you need to be effective. Valuation is the single best guide of its kind, helping financial professionals worldwide excel at measuring, managing, and maximizing shareholder and company value. This new seventh edition provides insights on the strategic advantages of value-based management, complete detailed instruction, and nuances managers should know about valuation and valuation techniques as applied to different industries, emerging markets, and other special situations"--